Thành phần hóa học cây Cóc đỏ (Lumnitzera littorea) thu hái tại tỉnh Thừa Thiên Huế, Việt Nam - Huyền, Phạm Thị; Thiện, Đào Đức; Lộc, Trần Văn; Sung, Trần Văn; Phương Thảo, Trần Thị (Vietnam Journal of Chemistry, 2017)
From the ethyl acetate and methanol extracts of the leaves and stems of Lumnitzera littorea (Jack) Voigt., collected in Thua Thien-Hue province, eleven compounds have been isolated. Their structures were elucidated as two resorcinolic lipids (1,3-dihydroxy-2-methyl-5-tridecylbenzene 1, 1,3-dihydroxy-5-nonadecylbenzene 2), two flavonoids (quercetin 3 and astragalin 4), two hexitols (1-acetyl-D-mannitol 5 and D-mannitol 6), α-D-glucopyranosyl-β-D-glucopyranoside (Neotrehalose 7) as octaacetate, fructopyranose as tetraacetate (8), β-sitosterol glycoside (9), β-sitosterol (10) and stigmasterol (11) as a mixture of 1:1 ratio. All of these compounds have been isolated for the first time from Lumnitzera littorea. Keywords. Lumnitzera littorea, sterols, resorcinolic lipids, flavonoids, hexitols.